MORPHOLOGICAL PROCESS OF ENGLISH AND ARABIC - Muhammad Nur (Edulitics (Education, Literature, and Linguistics) Journal, 2016)
In this research the researcher is interested in conducting a research on the morphological process of English. Morphological process is the devices by which the constituent words of a paradigm are differentiated from one another. It deals with how a certain word is formed. A word can be derived from another word or can be formed from a certain available word. This research is intended to make a comparison between English andArabic morphological process. There are three research questions . They are as the followings: 1. What kinds of affixes are found in English and Arabic? 2. Are there the internal change forms in English and Arabic? 3. Are there zero modification forms in English and Arabic? The significance of the study are: Theoretically, this research will give more data of English and Arabic morphological processes that can be used to support and build a strong theory concerning the morphological process in both languages (English and Arabic). Practically, the result of this research can be used by language teachers as the material in teaching morphology as one of the branches of linguistics. For the students, the results of this research will be useful for them as a guide in learning word formation in English and Arabic. Keywords: Arabic Morphological proccess, affixes, internal change, sero modiffication